Transformasi Konsep Pemerintahan Nabi Muhammad SAW dalam Bingkai Hukum Tata Negara Islam dan Implementasinya di Indonesia Modern - Muhammad Refan Sauqi; Nisfu Ruwaihan; Tenry Hermawan (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
This study examines the transformation of Prophet Muhammad’s concept of governance within the framework of Islamic Constitutional Law and its relevance and implementation in Indonesia’s modern governmental system. The governance established by the Prophet in Medina laid the foundation of a state order grounded in monotheism, justice, consultation, and the rule of law. These principles reflect the essence of Islamic governance that upholds morality, equality, and social responsibility. This research employs a qualitative approach using normative-historical methods by exploring classical and constitutional Islamic sources such as the Medina Charter, the Qur’an, and Hadith, then comparing them with Indonesia’s constitutional principles as embodied in the 1945 Constitution. The findings indicate a strong alignment between the values of Prophet Muhammad’s governance and Indonesia’s constitutional system, particularly in aspects of social justice, people’s participation, and respect for the law. Nonetheless, differences exist in terms of the foundation of power legitimacy and the source of legal authority. The study concludes that the governance model of Prophet Muhammad can serve as a moral and ethical reference for strengthening modern Indonesian governance without altering the democratic principles of Pancasila. Thus, the universal values of Islamic governance remain relevant and adaptable to the modern state context..